Discourse on News of the Changes in PCR and Antigen Policies as Travel Requirements in Indonesia - Azka, Hana Sabila; Prasetyo, Bambang Dwi; Kriyantono, Rachmat (Advances in Social Sciences Research Journal, 2022)
Covid-19 which occurred in 2020 became a health problem that happens 18 years ago in China, in regards to the case of acute respiratory syndrome or SARS. News as an actual source of information has become a benchmark for society in seeking information about Covid-19. In this study, the researchers aim to conduct critical discourse analysis on the news portal tribunnews.com in reporting on changes in PCR test and Antigen policies as travel requirements in Indonesia, published on March 2022. The method used in this study is critical discourse analysis from Teun Van Dijk, through three elements of discourse which are: macro structure, superstructure, and microstructure. The researchers divide this report into three phases; the initial phase, the middle phase, and the final phase which the result shows a picture of the situation starting from confusion and criticality, rejection of the policy, and the phase of acceptance of the new policy. This also has an influence on several sectors, such as education and economy.